Correlation of gene structure and psychophysical measurement in red-green color vision deficiency in Chinese - Zhang, Q; Xiao, X; Shen, H; Li, S; Jiang, F (Japanese journal of ophthalmology, 2000)
To study the correlation of genotype for X-linked red-green gene array with color vision phenotype in 58 subjects with red-green color vision deficiency. The molecular structure of red and green pigment genes on 58 X chromosomes was studied exon-by-exon by using heteroduplex-SSCP analysis and sequencing. The color vision of these subjects was determined by a Neitz anomaloscope. Variations in the red and green pigment genes were detected in 43 subjects and a hybrid gene was found in 27 subjects. About 50% of the fusion sites occurred at intron 2-3. All 3 anomalous trichromats with intron 4 fusion were mild type but another 3 with intron 2-3 fusion were severe type. No subjects with mild type of color vision defects had a fusion site at intron 2-3 or its upstream. Three subjects with complete deletion of the green pigment gene manifested deuteranomaly. Protans can be differentiated from deutans on the basis of genotype. It is still difficult to establish a clear correlation of different anomalous trichromats with genotype. The fusion site of a hybrid gene affects the phenotype to some degree. Intron 2-3 is the common place for gene crossover.